2018
DOI: 10.1093/milmed/usy086
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Forgotten: Motivating Military Veterans to Register with a Primary Healthcare Practice

Abstract: The primary healthcare staff took ownership and responsibility for this initiative. They were creative in introducing new ways of engaging with the local armed forces community. Many veterans' and staff were unaware of veterans' entitlement to priority medical services, or the wider provisions available to them. It is probable that veterans declaring their military status within primary healthcare, or registering with a general practitioner for the first time is likely to increase. Another review will be under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 63 publications
1
26
0
Order By: Relevance
“…Overall, the intent to provide student nurses with an insight into the AFC to help them construct an understanding of the biopsychosocial needs aligned to the AFC's care, health and wellbeing seems to have been achieved. It is envisioned that the sessions will positively enhance the wellbeing of military veterans and challenging long standing issues aligned to stigma (Harding, 2017;Finnegan et al, 2018a), with the potential to promote research and community good will.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the intent to provide student nurses with an insight into the AFC to help them construct an understanding of the biopsychosocial needs aligned to the AFC's care, health and wellbeing seems to have been achieved. It is envisioned that the sessions will positively enhance the wellbeing of military veterans and challenging long standing issues aligned to stigma (Harding, 2017;Finnegan et al, 2018a), with the potential to promote research and community good will.…”
Section: Discussionmentioning
confidence: 99%
“…We must recognise that our database is not fully representative of the veteran population in Scotland. In many cases, respondents were potentially unidentifiable/unreachable due to the types of ailments, geographical locations, and domiciliary arrangements as any veteran living within a care setting is often missed from such studies (Finnigan et al, 2018). 2 Furthermore, additional medical conditions specific to our cohort, such as hearing or sight loss, made communication by phone and/or other social media platforms very difficult.…”
Section: Methodology and Approachmentioning
confidence: 99%
“…Forty-seven percent were referred from the NHS 5 and 16% were referred from other veterans, findings which point to the importance of raising visibility in the health sector and establishing social networks amongst the veteran community. The role of the NHS as a means by which to identify veterans has been highlighted (Mark et al, 2020) and greater use of the NHS as a frontline means of identification has been urged (Finnigan et al, 2018).…”
Section: Methodology and Approachmentioning
confidence: 99%
“…Two years later, and despite significant investment in veterans' health and social care, a recent study indicated little change. However, in a cost effective six-week intervention this was increased to 26% [16].…”
Section: Introductionmentioning
confidence: 99%